Development of a procedure‐specific tool for skill assessment in left‐ and right‐sided laparoscopic complete mesocolic excision. (16th September 2022) - Haug, Tora Rydtun; Miskovic, Danilo; Ørntoft, Mai‐Britt Worm; Iversen, Lene Hjerrild; Johnsen, Søren Paaske; Valentin, Jan Brink; Gomez Ruiz, Marcos; Benz, Stefan; Storli, Kristian Eeg; Stearns, Adam T.; Brigic, Adela; Madsen, Anders Husted
Abstract: Aim: To (1) develop an assessment tool for laparoscopic complete mesocolic excision (LCME) and (2) report evidence of its content validity. Method: Assessment statements were revealed through (1) semi‐structured expert interviews and (2) consensus by the Delphi method, both involving an expert panel of five LCME surgeons. All experts were interviewed and then asked to rate LCME describing statements from 1 (strongly disagree) to 5 (strongly agree). Responses were returned anonymously to the panel until consensus was reached. Statements were directly included as content in the assessment tool if ≥60% of the experts responded "agree" or "strongly agree" (ratings 4 and 5), with the remaining responses being "neither agree nor disagree" (rating 3). Interclass correlation coefficient (ICC) was calculated for expert agreement evaluation. All included statements were subsequently reformulated as tool items and approved by the experts. Results: Four Delphi rounds were performed to reach consensus. Disagreement was reported for statements describing instrument handling around pancreas; visualisation of landmarks before inferior mesenteric artery ligation; lymphadenectomy around the inferior mesenteric artery, and division of the terminal ileum and transverse colon. ICC in the last Delphi‐round was 0.84. The final tool content included 73 statements, converted to 48 right‐ and 40 left‐sided items for LCME assessment. Conclusion: A procedure‐specific, video‐based tool, named complete mesocolic excision competency assessment tool (CMECAT), has been developed for LCME skill assessment. In the future, we hope it can facilitate assessment of LCME surgeons, resulting in improved patient outcome after colon cancer surgery.